TMOD-37. INTRAVITAL MONITORING DYNAMIC TUMOR MICRO-ENVIRONMENTAL EVOLUTION FOLLOWING HYPOXIA-INDUCED NECROSIS IN GLIOBLASTOMA. (11th November 2019) - Markwell, Steven; Ross, James; Olson, Cheryl; Nunez-Santana, Felix; Arvanitis, Constadina; Mukherjee, Subhas; Brat, Daniel
Abstract: The onset of necrosis correlates with malignant progression in virtually all human cancers. Whether necrosis arises from or promotes rapid tumor expansion remains unknown, primarily due to insufficient model systems necessary for capturing these dynamic changes as they develop. In glioblastoma (GBM; WHO grade IV), the most malignant primary brain tumor, the development of central necrosis precedes rapid, radial expansion precipitously leading to patient mortality. While genetic alterations in GBM have been highly characterized, the resultant biological adaptations leading to accelerated tumor growth require further mechanistic investigation. The onset of necrosis dramatically changes the tumor microenvironment (TME), evolving from a sheet-like growth of infiltrating malignant cells undergoing gradual expansion to a complex 3-D microsystem comprising diverse cell types and spatially segregated signaling networks. To reveal the dynamic temporal and spatial changes promoting progression, we are generating mouse models that more appropriately capture events found in human gliomas, accounting for unique microenvironmental stressors often lacking in GBM animal models, specifically central necrosis. We developed a novel method combining hypoxia-induced focal necrosis within high-grade gliomas with intravital microscopy to study TME restructuring and its impact on glioma progression in real time. As translational applications, we are investigating how hypoxia and necrosis promote glioma stem cell (GSC) enrichment in their peri-necrotic niche and how the massive influx of tumor-associated macrophages (TAMs) promotes glioma progression. Our studies use both genetically characterized patient-derived orthotopic GBM xenografts in humanized mice, alongside an immunocompetent RCAS/tv-a model, to determine how antagonizing these processes impacts disease progression and outcomes across multiple GBM subtypes. Our preliminary data indicate substantial differences pre- and post-necrosis regarding GSC and TAM enrichment and their biological impact, however, these mechanisms have not yet been studied. Our models capture glioma growth dynamics, GSC enrichment, and TAM influx, facilitating innovative therapeutic interventions to improve patient outcome.